THE INFLUENCE OF EASE OF USE, SHOPPING EXPERIENCE, AND SATISFACTION ON INTEREST TO REPURCHASE AT SHOPEE ONLINE STORES IN DENPASAR CITY - richadinata, kadek riyan putra; Carla Rettobjaan, Vitalia Fina (Universitas Ibn Khladun Bogor, 2023)
Technological developments have penetrated the world of the trade industry known as E-commerce, one of the most popular E-commerce today is Shopee. Various conveniences and comforts provided by business activists who take advantage of marketplace containers in the world of trade. But no less important is how to maintain consumer interest or repurchasing power which is difficult. This is what will be examined in this study. This study aims to determine the effect of ease of use, shopping experience, and satisfaction on repurchase intention at the online shop Shopee. The design of this study is descriptive correlational with a cross sectional approach. The sample used in this study was 100 people who were taken using a non-probability sampling technique with a consecutive sampling approach. Data were collected using a questionnaire, then analyzed bivariately using the Spearman'rank test and multivariate analysis using logistic regression. The results of the bivariate analysis showed that there was an effect of ease of use, shopping experience and satisfaction on repurchase intention with p < 0.05. In the multivariate analysis, the results show that the consumer's shopping experience has the most influence on repurchase intention with AOR=36,591; 95%. Consumer repurchase intention is strongly influenced by many factors, one of which is the ease of use factor, shopping experience and satisfied response felt by consumers